2019
DOI: 10.5487/tr.2019.35.4.403
|View full text |Cite
|
Sign up to set email alerts
|

Theracurmin (Highly Bioavailable Curcumin) Prevents High Fat Diet-Induced Hepatic Steatosis Development in Mice

Abstract: Curcumin, a hydrophobic polyphenol isolated from the Curcuma longa L. plant, has many pharmacological properties, including antioxidant, anti-inflammatory, and chemo-preventive activities. Curcumin has been shown to have potential in preventing nonalcoholic fatty liver disease (NAFLD). However, the low bioavailability of curcumin has proven to be a major limiting factor in its clinical adoption. Theracurmin, a highly bioavailable curcumin that utilizes micronized technology showed improved biological absorbabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…developed Theracurmin, which exhibited 30-fold higher absorption than commercially available curcumin [ 122 ]. Moreover, oral administration (150–600 mg/kg active dose) was recently shown to prevent hypertriglyceridemia and hepatic steatosis in high-fat diet-fed mice by reducing hepatic triglyceride content and inhibiting diet-induced lipid peroxidation [ 123 ]. Whether these beneficial effects were due to curcumin-mediated hepatic uncoupling remain to be determined; nonetheless, Theracurmin is currently in clinical trials (UMIN000007361) for the treatment of T2D.…”
Section: Therapeutic Relevance Of Mitochondrial Uncouplersmentioning
confidence: 99%
“…developed Theracurmin, which exhibited 30-fold higher absorption than commercially available curcumin [ 122 ]. Moreover, oral administration (150–600 mg/kg active dose) was recently shown to prevent hypertriglyceridemia and hepatic steatosis in high-fat diet-fed mice by reducing hepatic triglyceride content and inhibiting diet-induced lipid peroxidation [ 123 ]. Whether these beneficial effects were due to curcumin-mediated hepatic uncoupling remain to be determined; nonetheless, Theracurmin is currently in clinical trials (UMIN000007361) for the treatment of T2D.…”
Section: Therapeutic Relevance Of Mitochondrial Uncouplersmentioning
confidence: 99%
“…Rodent studies have shown that curcumin supplementation can prevent diet‐induced steatosis 16,27‐35 . Only a few rodent studies have examined curcumin as a treatment for established steatosis, also with positive results 36,37 .…”
Section: Discussionmentioning
confidence: 99%
“…Rodent studies have shown that curcumin supplementation can prevent diet‐induced steatosis. 16 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 Only a few rodent studies have examined curcumin as a treatment for established steatosis, also with positive results. 36 , 37 Randomized controlled trials have been carried out showing a decrease in ultrasound‐assessed HFC in patients diagnosed with steatosis when treating with curcumin.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, the authors found that curcumin was able to block Notch signaling in the liver of rats fed with HFD who developed hepatic steatosis, by the up-regulation of PPARα, (thus increasing FFAs oxidation), and by the down-regulation of lipogenic genes such as FAS and ACC (thus promoting lipids accumulation and hepatic steatosis development and worsening) [49]. Recently, theracurcumin, a more bioavailable synthetic form of curcumin, has been proven to reduce cholesterol levels by targeting both the HMG-CoA reductase and acyl-CoA: cholesterol acyltransferase (ACAT), two enzymes involved in cholesterol synthesis and esterification, respectively [51]. Niemann-pick C1-like 1 (NPC1L1) is a factor that mediates cholesterol absorption playing an important role in the pathogenesis of MASLD [71].…”
Section: Curcumin Modulates Lipid Metabolismmentioning
confidence: 99%